2009
DOI: 10.1016/j.febslet.2009.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Gentamicin inhibits HSP70‐assisted protein folding by interfering with substrate recognition

Abstract: Edited by Miguel De la RosaKeywords: Molecular chaperone Heat-shock protein with subunit molecular masses of 70 kDa Antibiotics Gentamicin a b s t r a c tWe previously reported that gentamicin (GM) specifically binds to heat-shock protein with subunit molecular masses of 70 kDa (HSP70). In the present study, we have investigated the effects of GM binding on HSP70-assisted protein folding in vitro. The C-terminal, and not the N-terminal of HSP70 was found to bind to GM. GM significantly suppressed refolding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 39 publications
(50 reference statements)
2
17
0
Order By: Relevance
“…82 The latter effect may have resulted from the gentamicin-specific inhibition of HSP70's chaperoning activity, thus promoting a positive feedback response. 83,84 In normal pigs, oral administration of the broad-spectrum antibiotic amoxicillin to mothers around parturition was found to affect the mother's fecal and the offspring's gut microbiota as well as the offspring's gut epithelial iHSPs: small intestinal iHSP27 remained unaffected, while iHSP70 decreased transiently, and both iHSP proteins increased in colonic mucosa. 45,63 Data were interpreted as being essentially related to amoxicillin-induced changes in maternal microbiota and subsequent microbiota transfer to offspring after birth.…”
Section: Antibioticsmentioning
confidence: 99%
“…82 The latter effect may have resulted from the gentamicin-specific inhibition of HSP70's chaperoning activity, thus promoting a positive feedback response. 83,84 In normal pigs, oral administration of the broad-spectrum antibiotic amoxicillin to mothers around parturition was found to affect the mother's fecal and the offspring's gut microbiota as well as the offspring's gut epithelial iHSPs: small intestinal iHSP27 remained unaffected, while iHSP70 decreased transiently, and both iHSP proteins increased in colonic mucosa. 45,63 Data were interpreted as being essentially related to amoxicillin-induced changes in maternal microbiota and subsequent microbiota transfer to offspring after birth.…”
Section: Antibioticsmentioning
confidence: 99%
“…We previously demonstrated that gentamicin suppresses the protein refolding activity of HSC70 [29,30]. To examine whether other AGs have similar effects on HSC70 activity, the refolding of denatured firefly luciferase was used as a model substrate.…”
Section: Resultsmentioning
confidence: 99%
“…We previously demonstrated that gentamicin specifically inhibits the HSC70/substrate interaction, but not the HSC70/HSP40 interaction [30]. To examine whether other AGs have the same effect, a substrate binding assay of HSC70 using F-RCMLA as a model substrate was performed [31,32].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations